2021
DOI: 10.1002/alz.058474
|View full text |Cite
|
Sign up to set email alerts
|

Microglia subtype transcriptomes differ between Alzheimer Disease and control human postmortem brain samples

Abstract: Background Microglia‐mediated neuroinflammation is hypothesized to contribute to disease progression in neurodegenerative diseases such as Alzheimer’s Disease (AD). Microglia subtypes are complex, with beneficial and harmful phenotypes. Understanding the gene expression networks which define the spectrum of microglia phenotypes is critical to identifying specific targets for neuroinflammation modulating therapies. Method Our study utilized post‐mortem brain tissue from 22 total (7 male) participants; 12 (3 mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…However, early results from transgenic mouse and autopsy studies have shown that the increased TSPO density in the AD brain co-localizes to microglia rather than astrocytes (Venneti et al, 2008;Gulyas et al, 2009). Beyond that, microglial activation is a complex process that produces multiple phenotypes (Prater et al, 2021;Wang, 2021), while TSPO PET tracers cannot robustly distinguish between these distinct phenotypes. Thus, caution must be used when interpreting TSPO PET imaging in animals or patients.…”
mentioning
confidence: 99%
“…However, early results from transgenic mouse and autopsy studies have shown that the increased TSPO density in the AD brain co-localizes to microglia rather than astrocytes (Venneti et al, 2008;Gulyas et al, 2009). Beyond that, microglial activation is a complex process that produces multiple phenotypes (Prater et al, 2021;Wang, 2021), while TSPO PET tracers cannot robustly distinguish between these distinct phenotypes. Thus, caution must be used when interpreting TSPO PET imaging in animals or patients.…”
mentioning
confidence: 99%